2020
DOI: 10.1038/s42005-019-0276-8
|View full text |Cite
|
Sign up to set email alerts
|

Fingerprints of a second order critical line in developing neural networks

Abstract: Patterns of biological activity with properties similar to critical states of statistical mechanics have received much attention, as they were mostly seen as indicators of computational optimality. Commonly, a single regime around an isolated critical point is expected. Our experimental data and our network simulations of developing neural cultures indicate the possibility of transitions between different critical regimes. In the latter, the addition of further fundamental neurophysiological principles to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 70 publications
(148 reference statements)
2
12
0
Order By: Relevance
“…3b). In a previous study of the cell culture data [29] we found first fingerprints of avalanche criticality after 10 DIV, where our mean excess entropy shows a prominent increase, in agreement with what the logistic map example suggests (Fig. 2).…”
Section: Simulated Vs Real-world Networksupporting
confidence: 91%
See 3 more Smart Citations
“…3b). In a previous study of the cell culture data [29] we found first fingerprints of avalanche criticality after 10 DIV, where our mean excess entropy shows a prominent increase, in agreement with what the logistic map example suggests (Fig. 2).…”
Section: Simulated Vs Real-world Networksupporting
confidence: 91%
“…After criticality at W 0.13, multiple modes of independent subnetworks emerge that, upon the increase of W , are bound by and then are released from sets that share synchronization in an intermittent-like manner [8], rather similar to what we observe in the biological example. The failure of this model to reach the experimental excess entropy levels suggests that its parameter W should be changed into a temporally variable quantity [29].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, it is not clear whether deviations from criticality caused by different intervention methods follow an identical phase 5 / 44 transition trajectory. Recent studies have proposed the concept of a "critical line" instead of a "critical point" and suggested that multiple phase transition trajectories may exist (Kanders et al, 2020). Therefore, the successful recovery of the phase transition trajectory from a large-scale brain network will not only help to answer key questions regarding what the phase transition is if the brain is critical but also have important implications in brain functional imaging and large-scale brain modeling.…”
Section: / 44mentioning
confidence: 99%